2023
DOI: 10.1002/eap.2791
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient enrichment promotes invasion success of alien plants via increased growth and suppression of chemical defenses

Abstract: In support of the prediction of the enemy release hypothesis regarding a growth–defense trade‐off, invasive alien plants often exhibit greater growth and lower anti‐herbivory defenses than native plants. However, it remains unclear how nutrient enrichment of invaded habitats may influence competitive interactions between invasive alien and co‐occurring native plants, as well as production of anti‐herbivore defense compounds, growth‐promoting hormones, and defense‐regulating hormones by the two groups of plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Several studies have found empirical support for this prediction (Magaña-Hernández et al, 2020;Mokany et al, 2006;Oduor, 2022;Shan et al, 2022;Xue et al, 2023). The present results also support the prediction of the optimal partitioning theory.…”
Section: Ta B L Esupporting
confidence: 89%
“…Several studies have found empirical support for this prediction (Magaña-Hernández et al, 2020;Mokany et al, 2006;Oduor, 2022;Shan et al, 2022;Xue et al, 2023). The present results also support the prediction of the optimal partitioning theory.…”
Section: Ta B L Esupporting
confidence: 89%
“…Moreover, under herbivory pressure, native plant species should maintain a stable anti-herbivore defence with low trait plasticity in response to variation in soil nutrient availability (Dawson et al, 2004;Shan et al, 2022). In other words, for native species F I G U R E 8 Relationships between above-ground biomass (AGB) and principal component analysis axis one (PC1) for root traits of Phragmites australis (a) and Spartina alterniflora (b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, salt pressure was found to constrain the growth plasticity of native P. australis in response to N heterogeneity (Guan et al., 2021). Moreover, under herbivory pressure, native plant species should maintain a stable anti‐herbivore defence with low trait plasticity in response to variation in soil nutrient availability (Dawson et al., 2004; Shan et al., 2022). In other words, for native species under changing environmental conditions, plasticity is not always advantageous, as plastic adaptive responses to a given environmental factor can turn out to be maladaptive when another factor is stressful (Valladares et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The enemy release hypothesis suggests that invasive alien plants, due to a growth–defense trade‐off, often demonstrate superior growth and weaker antiherbivory defenses compared with native plants. Shan et al (2023) conducted a multispecies greenhouse experiment to examine how nutrient enrichment in invaded habitats influenced this growth–defense trade‐off between invasive and co‐occurring native plants. Their study revealed that invasive species, relative to native ones, displayed an enhanced ability to adjust their flavonoid‐based defenses in response to shifts in soil nutrient availability and herbivory pressure.…”
Section: Performance Of Successful Iasmentioning
confidence: 99%